Extreme Outdoor Sdn Bhd / Ruzita Sahak ... [et al.] - Sahak, Ruzita; Mohd Salleh, Noor Esmi; Dzulkarnain Sim, Julinawatie; Abd Aziz, Noor Aniza; Md Akhir, Norazlina (2000)
Extreme Outdoor Sdn Bhd was started operation on 1 January 2005. The main acitivity of this business are selling camping requirement, extreme recreational and outdoor activities. It was a partnership business. Extreme Outdoor company was located at Sungai Petani, Kedah Darul Aman.